CDR1as regulated by hnRNPM maintains stemness of periodontal ligament stem cells via miR‐7/KLF4 - Gu, Xiuge (J Cell Mol Med, 2021)
CDR1as is a well‐identified circular RNA with regulatory roles in a variety of physiological processes. However, the effects of CDR1as on stemness of periodontal ligament stem cells (PDLSCs) and the underlying mechanisms remain unclear. In this study, we detect CDR1as in human PDLSCs, and subsequently demonstrate that CDR1as maintains PDLSC stemness. Knockdown of CDR1as decreases the expression levels of stemness‐related genes and impairs the cell's multi‐differentiation and cell migration abilities, while overexpression of CDR1as increases the expression levels of stemness‐related genes and enhances these abilities. Furthermore, our results indicate that the RNA‐binding protein hnRNPM directly interacts with CDR1as and regulates its expression in PDLSCs. In addition, we show that CDR1as promotes the expression of stemness‐related genes in PDLSCs by inhibiting miR‐7‐mediated suppression of KLF4 expression. Collectively, our results demonstrate that CDR1as participates in the molecular circuitry that regulates PDLSC stemness.